Polyunsaturated Fatty Acid EAB-277® Supplementation Improved Heart Rate Variability and Clinical Signs in Tracheal Collapse Dogs - Mektrirat, Raktham; Rueangsri, Thareerat; Keeratichandacha, Waraporn; Soonsawat, Sasiwimon; Boonyapakorn, Chavalit; Pongkan, Wanpitak (Frontiers in Veterinary Science, 2022)
Canine tracheal collapse is a progressive disease in small breed dogs resulting from chronic inflammation of the tracheal mucosal lining. Polyunsaturated fatty acid EAB-277® is one of the nutraceuticals that can alleviate inflammation and oxidative stress. Heart rate variability (HRV) is a prognostic tool related to sympathovagal balance and oxidative stress level, which is widely used with cardiorespiratory diseases. However, the effect of EAB-277® on HRV in tracheal collapse dogs has rarely been investigated. In this study, twenty-six tracheal collapse dogs were divided into two groups. In the control group, the dogs received the standard treatment, whereas the dogs in the EAB-277® group received standard treatment combined with EAB-277®. After being treated for five weeks, changes in radiographic findings, blood profiles, serum malondialdehyde, inflammatory markers, and HRV were evaluated. This study found that clinical signs were improved in both groups (p<0.05). However, serum malondialdehyde (MDA), Interleukin-6 (IL-6), and Tumor necrosis factor-alpha (TNF-) were decreased only in the EAB-277® group after treatment for five weeks (p<0.05) and the mean percent change of MDA, IL-6, and TNF- at week five compared to baseline in the EAB-277® group was greater than in the control group (p<0.05). Additionally, greater sympathovagal imbalance indicated by decreased standard deviation of all normal R-R intervals (SDNN) and standard deviation of the averaged R-R intervals for all 5-minutes segments (SDANN) was found in the control group at week five compared to baseline (P<0.05), whereas EAB-277® improved SDNN and SDANN and decreased low frequency/high-frequency component (LF/HF ratio) after being treated for five weeks (P<0.05). This study demonstrates that EAB-277® improves clinical signs and attenuates HRV impairment by reducing oxidative stress and inflammation in tracheal collapse dogs.